2022
DOI: 10.17645/up.v7i2.5591
|View full text |Cite
|
Sign up to set email alerts
|

From Desk to Field: Countering Agrourbanism’s “Paper Landscapes” Through Phenomenology, Thick Description, and Immersive Walking

Abstract: The primary focus of the urban agriculture literature has been on landscapes as biophysical spaces in which to grow food rather than on them as humanized places in which to grow experience. There is a need to leave the desk behind and enter the field to invigorate case study descriptions through the reflexive tool of narrative scholarship.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In their piece, the author points out that indeed, the urban agriculture literature has primarily focused on landscapes as biophysical spaces in which to grow food, rather than as humanized spaces in which to grow experience, making the case for different dimensions of what is well-being and consideration for achieving outcomes, such as the UN's Sustainable Development Goal 11. Specifically, in order to invigorate case study descriptions through the reflexive tool of narrative scholarship, it is necessary to leave the desk behind and enter the field (France, 2022). Das (2022), in their contribution from India, found that in organized green spaces, environmental justice must be developed and managed.…”
Section: Thematic Issue: From Smart Urban Forests To Edible Citiesmentioning
confidence: 99%
“…In their piece, the author points out that indeed, the urban agriculture literature has primarily focused on landscapes as biophysical spaces in which to grow food, rather than as humanized spaces in which to grow experience, making the case for different dimensions of what is well-being and consideration for achieving outcomes, such as the UN's Sustainable Development Goal 11. Specifically, in order to invigorate case study descriptions through the reflexive tool of narrative scholarship, it is necessary to leave the desk behind and enter the field (France, 2022). Das (2022), in their contribution from India, found that in organized green spaces, environmental justice must be developed and managed.…”
Section: Thematic Issue: From Smart Urban Forests To Edible Citiesmentioning
confidence: 99%